PENGARUH WORKING CAPITAL TERHADAP FIRM VALUE PADA PERUSAHAAN SEKTOR NON-KEUANGAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA PERIODE 2012-2016 - Silvia Chandra Putri; Werner Ria Murhadi; Mudji Utami (Perpustakaan Universitas Surabaya, 2018)
The objective of this research is to examine the effect of cash conversion cycle (CCC), accounts receivable conversion period (ACP), inventories conversion period (ICP), and accounts payable deferral period (APP) as independent variable to firm value of non-financial firm (eight sectoral) listed on Indonesia Stock Exchange as dependent variable. The research uses quantitative perspective with linier regression and model in a panel data for all of the research’s observation that used in this research. The number of observation in this research are 945, consists of 189 firms that has been enlisted on Indonesia Stock Exchange for 2012-2016 period. The result shows that cash conversion cycle (CCC), accounts receivable conversion period (ACP), and inventories conversion period (ICP) have negative significant effect onfirm value. Beside accounts payable deferral period (APP)appears to be having no significant effect on firm value.